The Effect of Acceptance and Commitment Therapy on Hypochondria and Cognitive Emotion Regulation among Divorced Women - Hamideh Iri; Behnam Makvandi; Saeed Bakhtiarpour; Fariba Hafezi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Hypochondriasis is a psychological disorder that affects divorced womenchr('39')s quality of life and mental health. The aim of this study was to investigate the effectiveness of acceptance and commitment therapy (ACT) on hypochondria and cognitive emotion regulation among divorced Women in Tehran. Methods: The method was experimental with a pre-test, post-test design, and a control group. In the present study, the research population includes divorced women who have been affected by divorce-related psychological problems and were referred to Tehran consultation centers in 2018. In this study, The sample consisted of 30 divorced women selected by purposive sampling and randomly divided into experimental and control groups (n= 15 each). The research tools included the Health Anxiety Inventory (HAI) and the Cognitive Emotion Regulation Questionnaire (CERQ). The ACT intervention was performed on the experimental group for ten 90-minute sessions. Pearsonchr('39')s correlation coefficient, Levenechr('39')s test, Shapiro-Wilk test, and multivariate analysis of covariance (MANCOVA) were used to analyze the data. The significance level of the study was considered to be α=0.05. Results: The mean and standard deviation (SD) of hypochondria post-test scores in the experimental and control groups were 35.13±1.92 and 37.33±3.07, respectively. The results indicated that ACT decreased hypochondria in the women (P=0.04). Also, the intervention effectively increased positive emotion regulation in the women (P=0.01). Conclusion: In addition to decreasing anxiety and increasing emotion regulation ability under difficult situations, ACT can increase social and psychological adaptability. Also, ACT can effectively decrease interactive and stress and anxiety in divorced women.